Pro-Inflammatory and B Cell Regulating Capacities of TWEAK in Rainbow Trout (Oncorhynchus mykiss) - Abós, Beatriz; Pérez-Fernández, Elena; Morel, Esther; Perdiguero, Pedro; Tafalla, Carolina (Frontiers in Immunology, 2021)
Tumor necrosis factor (TNF)-like weak inducer of apoptosis or TWEAK is a member of the TNF superfamily involved in the regulation of many biological processes. In mammals, TWEAK has been shown to play a role in some autoimmune or inflammatory conditions, but its immune role is not yet clearly defined. In teleost fish, although a few studies have identified homologues to mammalian TWEAK, their biological effects have never been investigated. In the current study, we have studied the transcriptional regulation of two TWEAK homologues (TWEAK 1 and 2) identified in rainbow trout (Oncorhynchus mykiss) throughout different tissues, in response to parasitic or viral infections, or in head kidney (HK) leukocytes stimulated with different stimuli. Although the transcription of both homologues was modulated when HK leukocytes were exposed to several immune stimuli, only TWEAK 1 was significantly modulated upon pathogenic exposure. Thus, we performed a characterization of the functions exerted by this cytokine in HK leukocytes. Recombinant TWEAK 1 strongly up-regulated the transcription of pro-inflammatory genes and antimicrobial peptides in HK leukocytes, with differential transcriptional effects in IgM+ B cells, IgM- lymphocytes and myeloid cells. TWEAK 1 also increased the survival and promoted the differentiation of B cells in HK leukocyte cultures. Our results demonstrate that in teleost fish, TWEAK 1 is involved in the response to different types of pathogens, through the modulation of antimicrobial and pro-inflammatory genes in different leukocytes subsets. Furthermore, a role for TWEAK as a B cell differentiation factor has also been established in rainbow trout.